Cofilin activation in pancreatic acinar cells plays a pivotal convergent role for mediating CCK-stimulated enzyme secretion and growth - Ramos-Alvarez, Irene; Lee, Lingaku; Jensen, Robert T. (Frontiers in Physiology, 2023)
The actin regulatory protein, cofilin plays a key signaling role in many cells for numerous cellular responses including in proliferation, development, motility, migration, secretion and growth. In the pancreas it is important in islet insulin secretion, growth of pancreatic cancer cells and in pancreatitis. However, there are no studies on its role or activation in pancreatic acinar cells. To address this question, we studied the ability of CCK to activate cofilin in pancreatic acinar cells, AR42J cells and CCK1-R transfected Panc-1 cells, the signaling cascades involved and its effect on enzyme secretion and MAPK activation, a key mediator of pancreatic growth. CCK (0.3 and 100 nM), TPA, carbachol, Bombesin, secretin and VIP decreased phospho-cofilin (i.e. activate cofilin) and both phospho-kinetic and inhibitor studies of cofilin, LIM kinase (LIMK) and Slingshot Protein Phosphatase (SSH1) demonstrated these conventional activators of cofilin were not involved. Serine phosphatases inhibitors [calyculin A and okadaic acid], however inhibited CCK/TPA-cofilin activation. Studies of various CCK-activated signaling cascades showed activation of PKC/PKD, Src, PAK4, JNK, ROCK mediated cofilin activation, but not PI3K, p38, or MEK. Furthermore, using both siRNA and cofilin inhibitors, cofilin activation was shown to be essential for CCK-mediated enzyme secretion and MAPK activation. These results support the conclusion that cofilin activation plays a pivotal convergent role for various cell signaling cascades in CCK mediated growth/enzyme secretion in pancreatic acini.